Review of obstetrical emergencies and fetal out come in a tertiary care centre - Prasad, Dipali; Nishat, Huma; Tiwary, Bhawana; Nisha, Swet; Sinha, Archana; Goel, Neeru (International Journal of Research in Medical Sciences, 2018)
Background: Obstetric emergencies can occur suddenly and unexpectedly. Obstetrics is unique in that there are two patients to consider and care for, a mother and a baby or fetus. Identification and referral of high risk pregnancies are an integral part of maternal and child health services. Timeliness and appropriateness can reduce the incidence of obstetric emergencies. Present study was carried out to know the incidence, nature and outcome of obstetric emergencies. Methods: Retrospective study of obstetric emergencies admitted to Obstetrics and Gynaecology department of Indira Gandhi Institute of Medical science, Patna from March 2015 to September 2017. Results: The common clinical presentation was Ectopic Pregnancy (19.64%), Heart Disease (16.64%), Abortion (13.69%), Severe Anaemia (16.66%), Purpureal Sepsis (9.52%), Sever pregnancy induced hypertension (3.57%), Eclampsia/ HELLP Syndrome (2.38%), Multiple Pregnancy (1.19%) Malignancy Disorder with Pregnancy (2.97%) and HIV in pregnancy (0.59%). Intervention done include Dilation and evacuation (13.69%), Caesarean section (28.57%), Vaginal delivery (22.62%), Caesarean Hysterectomy (2.38%), Exploratory Laparotomy (20.83%) and conservative management in (11.90%) of patients. Maternal outcome include shock due to rupture ectopic and post-partum (16.68%), Blood Transfusion done in (27.99%), Septicaemia (15.48%), ICU admission (8.92%), HDU (12.5%), Pulmonary oedema (6.54%), DIC (4.16%), CCF (3.57%), Ventilatory Support (1.78%) and Maternal Mortality (2.38%). Fatal outcome includes live birth (58.8%), NICU Admission (27.45%), Ventilatory Support (7.84%) and Neonatal mortality (5.88%). Conclusions: High risk pregnancy identification and proper antenatal, intranatal and postnatal care will reduce the incidence of obstetrical emergencies. Peripheral health care system need to be strengthen and early referral need to be implemented for better maternal and fetal outcome.